От жжизни к жизни: [сборник] / Евгений Гришковец - Гришковец Евгений (Махаон, 2012)
Экземпляры: ф.20 (ретро) / Инвентарный номер: 48880 / Цена: / Сис.шифр: 84Р6 / Авт.знак: Г 85 / ББК: 84(2Рос = Рус)6